Efektivitas Musik Mozart untuk Meningkatkan Kreativitas Verbal - Melati, Inka Sukma; Suhadianto, Suhadianto (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2018)
AbstractVerbal creativity is one type of creativity that is needed by adolescents, especially in the field of education. New methods are needed to improve that creativity. This study aims to determine the effectiveness of the use of classical Mozart music on improving students' verbal creativity. Subjects in this study were determined by purposive sampling technique. This research uses pre-experimental design with one group pre and post test design. The subjects used only students of class VII-G as many as 29 students. In the execution subjects were given pre-test before the classical music of Mozart and given post-test after the classical music of Mozart. This research data was obtained by using Verbal Creativity Test from Munandar. Hypothesis testing is done by using technique of Paired Sample T-test obtained difference mean = 9,822, t-count equal to -6,799 with significance level equal to 0,000 (p <0,05). It can be concluded that Mozart's classical music effectively improves students' verbal creativity. Keywords: Verbal Creativity, Mozart Classic Music, Verbal Creativity Test